A dynamic pricing algorithm for a network of virtual resources. Issue 2 (12th December 2016) - Naudts, Bram; Flores, Mario; Mijumbi, Rashid; Verbrugge, Sofie; Serrat, Joan; Colle, Didier; De Turck, Filip; Kang, Joon‐Myung; Choo, Hyunseung; Kim, Myung‐Sup; Choi, Baek‐Young; Badonnel, Remi; et al.
Summary: A service function chain (SFC) is an ordered combination of abstract network functions (eg, network address translation and a firewall) that together define a network service (eg, video on demand). In an SDN/NFV‐based architecture, SFCs are composed of virtual network functions that need to be mapped to physical network components. Because the mapping of an SFC may be possible by multiple competing infrastructure providers (InPs), price will be a key differentiating factor. The pricing algorithm is therefore essential towards revenue management, yet current static pricing approaches suffer from several limitations. Among others, they do not consider the characteristics of the requests or the current state of the physical network. Using historical data, market data, and the current state of the physical network we investigate whether it is possible to increase total revenue of an InP compared to traditional static pricing approaches. This paper proposes a dynamic pricing algorithm to determine (1) at which utilization level it is rewarding to charge a higher price for a particular resource and (2) the alternative price that should be charged. Our simulation results for 8 different setups show that the proposed heuristic outperforms a static pricing approach significantly (by 8‐85% points for the considered scenarios). As a consequence, the proposed approach can be considered as an alternative for static pricing approaches. Still, it is unclear how the total revenue of an InP is affected when multiple or all competitors use a dynamic pricing algorithm; this will therefore remain the focus of future work. Abstract : This article proposes a dynamic pricing algorithm for networks of virtual resources. The algorithm determines at which utilization level it is rewarding to charge a higher price for a particular resource and the alternative price that should be charged. Applying this algorithm results in higher total revenue compared to the traditional static pricing approach.